(untitled) (Foro: Revista de Derecho, 2017)
Este trabajo propone una perspectiva del principio de separación de poderes con base en la relación objetiva que surge del control financiero ex post a cargo del Legislativo, sin excluir la relación subjetiva entre los poderes públicos y de estos con las instituciones encargadas de ese control, conocidas como entidades fiscalizadoras superiores. El análisis parte del diseño que las constituciones políticas establecen para esos órganos fiscalizadores, utilizando el caso de México y comparándolo con otros nueve países. The present article argues that the principle of separation of powers should be addressed from a perspective based on an objective relationship that emerges from the ex-post financial control carried out by the legislative branch. This perspective does not exclude the subjective relationship between the same public powers and the relationship between those powers and the institutions that are in charge of the ex-post financial control, known as Supreme Audit Institutions. The analysis is based on the design that political constitutions establish for the supreme auditing institutions. The case of Mexico is analysed and compared to other nine countries.